Artistic Talent and Sensibility: The Dramatic Uses of Art in Woody Allen’s Creation of Characters - Echart, Pablo (Arte, Individuo y Sociedad, 2016)
Art plays a key role in the lives of Woody Allen’s film characters. Many of them are writers, filmmakers or musicians; others, although not artists themselves, display a keen sensibility to appreciate art. The purpose of this article is to explore how this characterization trait significantly determines the nature of the characters, the ways in which they interact with each other, and even the fate they deserve within the plot. Art, in its many different manifestations, helps these characters infuse their lives with a boundless vitality, at the same time that it becomes a source of beauty and refuge. Furthermore, art plays a vital role in shaping romantic relationships as well as in enabling characters to achieve selfknowledge, both of which come close to the idea of happiness in Woody Allen’s poetic universe. At the same time, together with this recognition of the redeeming potential of art, a poetic punishment is inflicted frequently in Allen’s films on the characters that approach art with spurious intentions, as well as a stern warning of the vital unhappiness to which its enshrinement leads.